KUALITAS AUDIT DITINJAU DARI INDEPENDENSI, AUDIT TENURE, AUDIT FEE DAN DUE PROFESSIONAL CARE : AUDIT QUALITY IN VIEW OF INDEPENDENCE, AUDIT TENURE, AUDIT FEE AND DUE PROFESSIONAL CARE - Selsa Aprilady; Azwir Nasir; Mudrika Alamsyah Hasan; Riska Natariasari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this study was to analyze the influence of independence, the influence of audit tenure, the influence of audit fees, and the influence of due professional care on audit quality. Audit quality is the ability to detect and report material errors in financial statements. The population in this study is the Public Accounting Firm (KAP) in Pekanbaru, Riau, and the Public Accounting Firm (KAP) in Medan, North Sumatra which are registered in the IAPI 2022 Directory, namely 32 Public Accounting Firms (KAP). Purposive sampling was utilized to choose the study's sample. Thirteen public accounting firms were selected as samples in this study using predetermined criteria. The type of data used in this study is primary data using a questionnaire. Testing the research variables uses the Partial Least Square method using the SmartPLS 3.0 program. The results of the study show that independence, audit tenure, audit fee, and due professional care have an effect on audit quality